2020
DOI: 10.1002/alr.22579
|View full text |Cite
|
Sign up to set email alerts
|

Association of chemosensory dysfunction and COVID‐19 in patients presenting with influenza‐like symptoms

Abstract: Background: Rapid spread of the SARS-CoV-2 virus and concern for viral transmission by ambulatory patients with minimal to no symptoms underline the importance of identifying early or subclinical symptoms of Covid-19 infection. Two such candidate symptoms include anecdotally reported loss of smell and taste. Understanding the timing and association of smell/taste loss in Covid-19 may help facilitate screening and early isolation of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

52
872
14
46

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 719 publications
(1,003 citation statements)
references
References 8 publications
52
872
14
46
Order By: Relevance
“…Their results showed these chemosensory impairments were at least 10-fold more common in COVID-19-positive cases than COVID-19-negative cases, both presenting with similar influenza-like symptoms. 26 While the authors of this study did not reveal how many of these patients tested positive for influenza virus, 26 past studies have demonstrated that influenza is not significantly associated with change in smell. 27 Furthermore, postviral olfactory disorders due to other common viruses has an estimated prevalence of around 11%-40%, 28 which appears much less common than that seen with SARS-CoV-2 infection according to existing studies.…”
Section: Unusual Association Of Diseases/symptoms Patient's Perspectivementioning
confidence: 64%
“…Their results showed these chemosensory impairments were at least 10-fold more common in COVID-19-positive cases than COVID-19-negative cases, both presenting with similar influenza-like symptoms. 26 While the authors of this study did not reveal how many of these patients tested positive for influenza virus, 26 past studies have demonstrated that influenza is not significantly associated with change in smell. 27 Furthermore, postviral olfactory disorders due to other common viruses has an estimated prevalence of around 11%-40%, 28 which appears much less common than that seen with SARS-CoV-2 infection according to existing studies.…”
Section: Unusual Association Of Diseases/symptoms Patient's Perspectivementioning
confidence: 64%
“…The majority of our cohort do meet current criteria for testing in the UK, as it is only being undertaken in hospitalised patients, however, of those tested in our survey, 80% were found to be positive, While we do not know the means of testing, but in most cases, RT-PCR analysis of nasal swabs has been used, which have an estimated sensitivity of 72% [18]. Many patients also reported other symptoms described in COVID-19 infection, with half also reporting a new onset cough or fever, therefore making COVID-19 likely according to the results of Menni et al [12] and Yan et al [13]. However, our assumption that our cohort reflects patients with COVID-19 cannot be proven without test results even though it is supported by the evince base.…”
Section: Discussionmentioning
confidence: 80%
“…The strongest predictor is loss of smell and taste. In a similar study, Yan et al found smell and taste lost were reported by 68 and 71% of COVID positive patients respectively, compared to 16 and 17% of COVID negative patients, with loss of sense of smell being the strongest predictor (OR 10.9 for COVID-19 positivity) [13].…”
Section: Discussionmentioning
confidence: 83%
“…They concluded that the loss of smell or taste was 10 times more likely from COVID-19 infection than other causes of infection. 7 While the study will print next week in the NEJM, Washington post reported a story of "Healthy people in their 30s and 40s, barely sick with COVID-19, are dying from strokes". The paper mentioned that about a dozen of young strokes form three major hospitals in New York and Boston will report this series next week.…”
mentioning
confidence: 99%